Enhanced green upconversion luminescence in ZnO:Er3+, Yb3+ on Mo6+ co-doping for temperature sensor application. (19th December 2017) - Anjana, Radhakrishnan; Subha, Perumpallikkattil P; Kurias, Markose K; Jayaraj, Madambi K
Abstract: Erbium (Er) doped zinc oxide (ZnO) powder was prepared using co-precipitation method. Effect of ytterbium (Yb) and molybdenum (Mo) co-doping on upconversion emission was studied. The emission intensity has been enhanced on Yb co-doping due to energy transfer from Yb to Er. Co-doping Mo in ZnO:Er, Yb has brought a significant enhancement in green upconversion emission, when excited with 980 nm laser. The enhancement in green emission on Mo doping is because of the formation of Yb 3 + – MoO 4 2 − dimer. Since ZnO is a material having high thermal stability, the enhanced green emission in Mo, Er, Yb doped ZnO can be used for temperature sensor applications. The variation in relative intensity ratio of 2 H11/2 → 4 I15/2, 4 S3/2 → 4 I15/2 transition can be used to sense the sample temperature.